Repercusiones del covid-19 en el desempleo en las familias residentes en puerto Jelí del cantón Santa Rosa, año 2021 - Díaz Rivas, Yeleny Mishelle; Rubio Arévalo María Fernanda (Machala: Universidad Técnica de Machala, 2021)
The degree work is oriented to the study of the repercussions of COVID-19 on unemployment in the families residing in the Puerto Jelí Urban Parish of the Santa Rosa canton. The project will cover situations related to the unemployment experienced by families in the sector with the advent of Covid-19 and the sanitary measures adopted by the Ecuadorian Government. The partial paralysis of productive activities and the closure of commercial premises reflected negative consequences within the sector, directly affecting the economic income of the inhabitants The main objective of the research is to determine what is the impact of unemployment caused by the COVID-19 pandemic on families residing in the Urban Parish of Puerto Jelí, of the Santa Rosa Canton, 2021, therefore the specific objectives were aimed at establishing the types of productive activities that were affected by the state of emergency and the socio-family confinement ordered by the government as a result of the COVID-19 pandemic; determining the levels of unemployment in families due to the paralysis of productive activities; identifying how economically affected the families of Puerto Jelí the mandatory closure of productive activities decreed by the National Government; and establishing as an effect the paralysis of productive activities in the quality of family life and in good community living. The titling work at first presents the characteristic of descriptive research, consequently explanatory and propositional from the empirical – inductive epistemological approach, linked to a quantitative methodological approach that required the use of research techniques and information collection instruments to obtain the veracity of the facts and events that establishes the importance of objective information in social research, such as direct observation, interview and survey with a sample of 185 people who were applied in situ, which made it possible to achieve greater objectivity in the results. In addition, it is based on the sociological current of structural functionalism, which refers to the study of a society known as a social structure or system, where the subject builds knowledge from his previous experience and through an interaction with the environment. The empirical results reflect the presence of some social and economic problems that affect the inhabitants of the sector, of which is unemployment, the economic effects due to the paralysis and decrease in productive activities, the decrease in food services, the closure of commercial premises and the scarce employment opportunity due to the little existence of tourism, In addition, these events have decreased the quality of life, preventing the satisfaction of their needs in the different families of the place, therefore the development of an intervention proposal was considered that is to design a training plan on family enterprises in agreement with the Municipal GAD, this will allow the site to improve working conditions, obtaining an adequate salary remuneration and the well-being of each family, so that they achieve the satisfaction of their needs.
El trabajo de titulación se orienta al estudio de las repercusiones del COVID-19 en el desempleo en las familias residentes de la Parroquia Urbana Puerto Jelí del cantón Santa Rosa. El proyecto abarcará situaciones vinculadas al desempleo que viven las familias del sector con el advenimiento de la Covid-19 y las medidas sanitarias adoptadas por el Gobierno Ecuatoriano. La paralización parcialmente de las actividades productivas y el cierre de locales comerciales reflejaron consecuencias negativas dentro del sector, afectando de manera directa a los ingresos económicos de los habitantes. El objetivo principal de la investigación es determinar cuál es el impacto del desempleo provocado por la pandemia COVID-19 en las familias residentes en la Parroquia Urbana Puerto Jelí, del Cantón Santa Rosa, 2021, por lo consiguiente los objetivos específicos se direccionaron a establecer los tipos de actividades productivas que se vieron afectadas por el estado de excepción y el confinamiento socio familiar ordenado por el gobierno como consecuencia de la pandemia de COVID-19; determinar los niveles de desempleo en las familias por la paralización de las actividades productiva; identificar cómo afecto económicamente a las familias de Puerto Jelí el cierre obligatorio de las actividades productivas decretadas por el Gobierno Nacional; establecer como afecto la paralización de las actividades productivas en la calidad de vida familiar y en el buen vivir comunitario. El trabajo de titulación en un primer momento presenta la característica de investigación descriptiva, consecuentemente explicativa y propositiva desde el enfoque epistemológico empírico – inductivo, vinculada con un enfoque metodológico cuantitativo que requirió la utilización de técnicas de investigación e instrumentos de recolección de información para obtener la veracidad de los hechos y acontecimientos que establece la importancia de información objetiva en la investigación social, tales como la observación directa, la entrevista y la encuesta con una muestra de 185 personas que fueron aplicados in situ, que posibilitaron alcanzar una mayor objetividad en los resultados. Además, se sustenta en la corriente sociológica del estructural funcionalismo, que hace referencia al estudio de una sociedad conocida como estructura o sistema social, donde el sujeto construye el conocimiento a partir de su experiencia previa y mediante una interacción con el medio. Los resultados empíricos reflejan la presencia de algunos problemas sociales y económicos que afectan a los habitantes del sector, de los cuales se encuentra el desempleo, las afectaciones económicas por la paralización y el descenso de las actividades productivas, el descenso de los servicios de alimentación, el cierre de locales comerciales y la escasa oportunidad laboral por la poca existencia de turismo, además, dichos acontecimientos han disminuido la calidad de vida, impidiendo la satisfacción de sus necesidades en las diferentes familias del lugar, por lo tanto se consideró el desarrollo de una propuesta de intervención que es el de diseñar un plan de capacitación sobre emprendimientos familiares en convenio con el GAD Municipal, esto permitirá que en el sitio se mejoren las condiciones laborales, obteniendo una adecuada remuneración salarial y el bienestar de cada familia, para que logren la satisfacción de sus necesidades.
Keywords: REPERCUSION; COVID-19; DESEMPLEO; ACTIVIDAD PRODUCTIVA